2005
DOI: 10.1523/jneurosci.4834-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stargazin Reduces Desensitization and Slows Deactivation of the AMPA-Type Glutamate Receptors

Abstract: The AMPA-type glutamate receptors mediate the majority of the fast excitatory synaptic transmission and critically contribute to synaptic plasticity in the brain, hence the existence of numerous trafficking proteins dedicated to regulation of their synaptic delivery and turnover. Stargazin (also termed ␥2) is a member of a recently identified protein family termed transmembrane AMPA receptor regulatory proteins (TARPs). TARPs physically associate with AMPA receptors and participate in their surface delivery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
253
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(284 citation statements)
references
References 28 publications
25
253
3
Order By: Relevance
“…Previous studies showed that ␥-2 increases the potency of glutamate for GluR1 (Priel et al, 2005;Tomita et al, 2005b). Similarly, we find that cotransfection of ␥-2 shifts the doseresponse curve for glutamate to the left and increases the EC 50 by threefold.…”
Section: ␥-7 Selectively Binds To Neuronal Ampa Receptorssupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies showed that ␥-2 increases the potency of glutamate for GluR1 (Priel et al, 2005;Tomita et al, 2005b). Similarly, we find that cotransfection of ␥-2 shifts the doseresponse curve for glutamate to the left and increases the EC 50 by threefold.…”
Section: ␥-7 Selectively Binds To Neuronal Ampa Receptorssupporting
confidence: 84%
“…␥-2 slows both the deactivation and desensitization of associated AMPA receptors (Priel et al, 2005;Tomita et al, 2005b). To determine whether ␥-7 also alters channel gating, we expressed GluR1 alone and in the presence of ␥-2, ␥-5, or ␥-7 in HEK293T cells (Fig.…”
Section: ␥-7 Selectively Binds To Neuronal Ampa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-termini of these receptor subunits are especially critical for the regulation of AMPA receptor function. While it is widely recognized that AMPA receptor function is highly complex, including important regulatory effects due to receptor trafficking (42,43) and interactions with additional membrane proteins, such as stargazin (44)(45)(46), it is evident that the phosphorylation state of Ser845 on GluR1 subunits is one of the most important factors for regulation of AMPAreceptor activity (47). For example, using a S845A mutant, it has been shown that phosphorylation of Ser845 results in a dramatic potentiation of channel activity in response to glutamate (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect on AMPAR trafficking, Stargazin controls AMPAR channel gating by slowing glutamateinduced AMPAR deactivation and desensitization, and enhancing the channel conductance (Priel et al, 2005;Tomita et al, 2005;Nicoll et al, 2006). Moreover, in the presence of TARPs, the AMPARs competitive antagonist 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) acts as a partial agonist (Menuz et al, 2007).…”
Section: Ampar Traffic Ampar Biosynthesis and Ampar Interaction Partnersmentioning
confidence: 99%